Carbonate-platform scale correlation of stacked high-frequency sequences in the Arab-D reservoir, Saudi Arabia - Al-Awwad, S.; Collins, Lindsay (Elsevier Science BV, 2013)
The Late Jurassic Arab Formation contains a number of hydrocarbon-bearing carbonates, the most important of which is the lowermost Arab-D reservoir. The reservoir lithofacies in Khurais Field are: couplets of 1) lime mud and 2) intraclastic lithofacies representing basinal turbidites; 3) pelletal lithofacies representing lower shoreface sands and silts; 4) stromatoporoid lithofacies representing a reef; 5) Cladocoropsis and 6) dasyclad lithofacies representing a lagoon; 7) peloidal and 8) oolitic lithofacies representing shore-attached sand sheets; 9) cryptomicrobial lithofacies representing supratidal flats; 10) anhydrites representing sabkha followed by salina deposits; and 11) stratigraphically reoccurring dolomite.These are arranged in two, partially preserved, third-order sequences, the upper of which represents the Arab-D Member and the lower of which represents the upper Jubaila Formation. Within these sequences lie six fourth-order high frequency sequences, composed of fifth-order parasequences and parasequence-scale cycles. The preserved upward shallowing trend of the Arab-D reservoir is manifested laterally by a regional eastward thickening interpreted to be the result of an eastward progradation across the shallow Late Jurassic epeiric shelf and into the relatively deep Arabian intrashelf basin. This study presents a correlation model that explains the drastic thickening and downward climb of the reservoir lithofacies that is observed between the outcrops south of Riyadh and the subsurface in Ghawar Field. This model is different from the one currently used and predicts an eastward porosity improvement in the upper part of the reservoir accompanied by a porosity reduction in the lower part, assuming a null diagenetic modification effect.